The Blue Max - Ferry, Christian; Pursall, David; Seddon, Jack, 1924-2001.; Hanley, Gerald; Guillermin, John, 1925-; Peppard, George; Mason, James, 1909-1984.; Andress, Ursula, 1936-; Kemp, Jeremy, 1934-; Vogler, Karl Michael, 1928-; Diffring, Anton, 1918-1989.; Towb, Harry, 1925-; et al. ([United States] : 20th Century Fox Home Entertainment, 2003)
A low-born infantryman becomes a pilot during World War I, almost deliberately stepping on the sensibilities of his aristocratic comrades in the process. A national hero, he wins the Blue Max, the highest award that can be bestowed upon an aviator. His fame is exploited by a general, who tolerates the affair between the pilot and the general's wife. The canny general knows that, eventually, the pilot will become expendable, and a "heroic" death can be arranged.
Originally released as a motion picture in 1966.
Based on the novel by Jack D. Hunter.
English track: Dolby digital 2.0 surround.
French track: Dolby digital 2.0 mono.
Spanish track: Dolby digital 2.0 mono.
Director of photography, Douglas Slocombe ; art director, Fred Carter ; editor, Max Benedict ; original music, Jerry Goldsmith ; costume designer, John Furniss ; production designer, Wilfrid Shingleton.
Keywords: Feature films; War films; Video recordings for the hearing impaired; Air pilots -- Germany; World War, 1914-1918 -- Aerial operations -- Drama; Feature films; War films; Video recordings for the hearing impaired